Pentraxins and atherosclerosis - Barbati, E.; Bottazzi, B.; Catapano, A.; Garlanda, C.; Latini, R.; Mantovani, A.; Norata, Giuseppe; Valentino, S. (2014)
© 2012 Springer-Verlag/Wien. All rights are reserved. Pentraxins are a family of evolutionarily conserved multifunctional patternrecognition proteins characterized by a cyclic multimeric structure. Based on the primary structure of the subunit, the pentraxins are divided into two groups: short pentraxins and long pentraxins. C-reactive protein (CRP) and serum amyloid P-component (SAP) are the two short pentraxins. The prototype protein of the long pentraxin group is pentraxin 3 (PTX3). CRP and SAP are produced primarily in the liver in response to IL-6, while PTX3 is produced by a variety of tissues and cells and in particular by innate immunity cells and endothelial cells in response to proinflammatory signals and Toll-like receptor (TLR) engagement. Structural analysis and gene-modified mice have provided a new level of understanding of the role of pentraxins in immunity, inflammation and homeostasis. Unlike the classic short pentraxins CRP and SAP, whose sequence and regulation have diverged between mouse and man, PTX3 is highly conserved in man and mouse. Thus, results obtained using genetic approaches in the mouse are likely to be informative for the function of PTX3 in man, whereas extrapolation from animals to man is more difficult for CRP and SAP.